2010
DOI: 10.1159/000321672
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Risk Factors and Correlates of Dementia in Older Malaysians

Abstract: Objective: The rapid expansion of the aged population in Malaysia is expected to greatly increase the number of persons with dementia in the country. However, data on dementia prevalence at the national level is lacking, and little is known about the sociodemographic risk factors and correlates of dementia. This paper describes a nationwide study of dementia prevalence and its sociodemographic risk factors and health correlates among older Malaysians. Methods: In the nationwide study, the Mental Health and Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
39
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 42 publications
12
39
1
1
Order By: Relevance
“…The findings confirm the association of increasing age and lack of schooling with prevalence of dementia syndrome [27,43,44]: a prevalence of 4.4% was obtained in the youngest group against 61.6% among the over 90-year-olds, and a prevalence of 7.8% was observed among those with most schooling against 50.6% among the illiterates. The prevalence in the most advanced age groups was higher than obtained in Brazilian population-based studies [28,30].…”
Section: Discussionsupporting
confidence: 83%
“…The findings confirm the association of increasing age and lack of schooling with prevalence of dementia syndrome [27,43,44]: a prevalence of 4.4% was obtained in the youngest group against 61.6% among the over 90-year-olds, and a prevalence of 7.8% was observed among those with most schooling against 50.6% among the illiterates. The prevalence in the most advanced age groups was higher than obtained in Brazilian population-based studies [28,30].…”
Section: Discussionsupporting
confidence: 83%
“…The data used in the study were drawn from a national survey on aging entitled ‘Mental Health and Quality of Life of Older Malaysians (MHQoLOM)', the full details of which have been presented elsewhere [13,19]. Briefly, MHQoLOM was a cross-sectional national survey which gathered extensive information on demographic characteristics, socioeconomic status, social and health status from a representative sample of older Malaysians.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a few studies in the United States have shown that African-Americans and Hispanics have higher prevalence rates of dementia than non-Hispanic whites [8]. In Malaysia, the results of a community-based study indicated marked differences in prevalence of dementia among different ethnic groups [13]. The results from a large community-based study in Singapore (which has the same ethnic groups as Malaysia) also showed that elderly Malays had twice the risk for Alzheimer's disease as Chinese [14].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that different cognitive abilities, including fluid and crystallised abilities, show different trajectories of change across the life span. Several moderating lifestyle factors, including educational, occupational and mental activity, have been identified, which may have a protective impact on the development of normal age-associated or pathological cognitive decline [29,33,34]. Accordingly, the high performance of older individuals in this study may be mediated by their high educational level.…”
Section: Discussionmentioning
confidence: 91%